2020
DOI: 10.1021/jasms.0c00179
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Oligonucleotide Characterization Using Liquid Chromatography–Mass Spectrometry: Insight into Critical Issues

Abstract: As interests increase in oligonucleotide therapeutics, there has been a greater need for analytical techniques to properly analyze and quantitate these biomolecules. This article looks into some of the existing chromatographic approaches for oligonucleotide analysis, including anion exchange, hydrophilic interaction liquid chromatography, and ion pair chromatography. Some of the key advantages and challenges of these chromatographic techniques are discussed. Colloid formation in mobile phases of alkylamines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…It is worth noting that although we had purified PB containing ODNs by anion-exchange HPLC, it was found that RP-HPLC purification using a mixture of methanol and a buffer containing hexafluoroisopropanol and triethylamine as an eluent was effective for isolation of these ODNs. 47 Thus, all of the ODNs but 22 were purified by RP-HPLC. Although there is room for further improvement of yields, some kinds of chimeric ODNs were successfully synthesized in the strategy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is worth noting that although we had purified PB containing ODNs by anion-exchange HPLC, it was found that RP-HPLC purification using a mixture of methanol and a buffer containing hexafluoroisopropanol and triethylamine as an eluent was effective for isolation of these ODNs. 47 Thus, all of the ODNs but 22 were purified by RP-HPLC. Although there is room for further improvement of yields, some kinds of chimeric ODNs were successfully synthesized in the strategy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For this work, hydrophilic interaction liquid chromatography (HILIC), which uses MS compatible mobile phases, was used as an alternative to more widely used ion-pair reversed-phase liquid chromatography (IPRP LC) to separate oligonucleotides prior to MS analysis. 6,7,11,[20][21][22] The absence of ion-pairing (IP) reagents during HILIC-MS analysis helps address some of the IP reagents-related technical hurdles, including The results demonstrated a good peak shape and an envelope of charge state distribution centered on the À4 charge state (Figure 1 inset), which was different from the wide charge state distributions commonly observed during IPRP LC-MS analysis of oligonucleotides. 20 Importantly, a predominant charge state offers better analytical sensitivity by consolidating the molecular ion count and is beneficial when using an extracted ion chromatogram for quantitation or when selecting a precursor ion in MS/MS.…”
Section: Hilic-ms Of Dnamentioning
confidence: 96%
“…5,14,15 In addition, structural modifications of oligonucleotides, such as internucleotide phosphodiester linkages replaced by phosphorothioate (PS) linkages, may pose potential challenges to the sequence elucidation by MS/MS because of the added resistance to bond cleavages by the modified linkages. 7,8,13,14,16 In this study, sequence characterization of custom synthesized DNA oligonucleotides of the same nucleotide sequence as nusinersen (an 18-mer with seven T units, marketed as Spinraza™ and approved by FDA in 2016) with or without PS modification was investigated using two ion activation techniques: resonant or trap-type collisioninduced dissociation ("CID") and beam-type CID or higher-energy collisional dissociation ("HCD"). 15,17,18 The feasibility and suitability of MS/MS fragmentation by CID or HCD were compared for the ability to produce diagnostic fragment ions for the sequence characterization of T-rich PS-modified oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations